J. O. La Metrie and His Philosophy - Tytmonas, Alfredas (Problemos, 1988)
The general characteristic of life and activity of the great French materialist J. O. La Metrie is presented in the article. The author of the article acquaints a reader with some studies about the philosopher, exposes his main ideas, and considers their influence on later philosophical thinking. J. O. La Metrie is characterised as a brave ideologist of the rising bourgeoisie. This fact explains the significance of his theoretical heritage for the social forces tending to future.